Functional characterization of the PHT1 family transporters of foxtail millet with development of a novel Agrobacterium-mediated transformation procedure - S. Antony Ceasar (Nature Portfolio, 2017)
Abstract Phosphate is an essential nutrient for plant growth and is acquired from the environment and distributed within the plant in part through the action of phosphate transporters of the PHT1 family. Foxtail millet (Setaria italica) is an orphan crop essential to the food security of many small farmers in Asia and Africa and is a model system for other millets. A novel Agrobacterium-mediated transformation and direct plant regeneration procedure was developed from shoot apex explants and used to downregulate expression of 3 members of the PHT1 phosphate transporter family SiPHT1;2 SiPHT1;3 and SiPHT1;4. Transformants were recovered with close to 10% efficiency. The downregulation of individual transporters was confirmed by RT-PCR. Downregulation of individual transporters significantly reduced the total and inorganic P contents in shoot and root tissues and increased the number of lateral roots and root hairs showing they have non-redundant roles. Downregulation of SiPHT1;2 had the strongest effect on total and inorganic P in shoot and root tissues. Complementation experiments in S. cerevisiae provide evidence for the ability of SiPHT1;1, 1;2, 1;3, 1;7 and 1;8 to function as high affinity Pi transporters. This work will aid development of improved millet varieties for global food security.